Issues of Blended Translation Teaching in Higher Education: a Systematic Literature Review (SLR) - Retnomurti, Ayu Bandu; Rasyid, Yumna; Dewanti, Ratna (Deiksis, 2024)
Blended teaching is prevailing among universities. This teaching mode can improve translation training effectiveness and facilitate the construction of translation discipline. As far as the translation field is concerned, the lack of translation technical resources and their inappropriate application are at the forefront. In response to these problems, this research aims on a systematic literature review: to clarify the concept of "blended teaching"; to build an online teaching platform; to improve the management and evaluation system related to blended teaching in Translation. The research method used is SLR and the PRISMA protocol through the stages which are supported by Publish or Perish 7, Mendeley, VOSviewer, and NVIVO 12 Plus applications. Regarding search results on Scopus, Google Scholar; Semantic Scholar, and Crossref, 875 articles were found, then filtered according to topic to 35 articles. The topic findings are blended translation teaching, higher education, definition, types, and impact of blended teaching, flipped teaching, flip classroom, distance teaching from a lecturer, distance teaching, active teaching, online or online teaching, and face to face faces, directly or indirectly interconnected. The 35 articles from 2019 to 2023 were analyzed according to the topics determined through NVIVO 12 Plus, and the results were described according to the research questions. This SLR puts forward solutions: to clarify the concept of "blended teaching"; to build an online teaching platform; and to improve the management and evaluation system related to blended teaching in higher education.